2014
DOI: 10.1007/s10456-014-9448-z
|View full text |Cite
|
Sign up to set email alerts
|

Robo4 vaccines induce antibodies that retard tumor growth

Abstract: Tumor endothelial specific expression of Robo4 in adults identifies this plasma membrane protein as an anti-cancer target for immunotherapeutic approaches, such as vaccination. In this report, we describe how vaccination against Robo4 inhibits angiogenesis and tumor growth. To break tolerance to the auto-antigen Robo4, mice were immunised with the extracellular domain of mouse Robo4, fused to the Fc domain of human immunoglobulin within an adjuvant. Vaccinated mice show a strong antibody response to Robo4, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Tumor endothelial-specific expression of Robo4 in adults reveals that this plasma membrane protein represents an antitumor target for immunotherapeutic approaches, such as vaccination. Robo4-Fc-vaccinated mice showed retarded lung carcinoma growth, increased vascular leakage and intensified inflammation compared with control Fc-immunized mice [110]. Robo4 vaccination with alum adjuvant, a mild inducer of Th2-dependent antibody responses, also reduced tumor growth via an antibody-mediated mechanism, particularly an IgG1-mediated mechanism, instead of cytotoxic T-cell responses.…”
Section: Robo4 and Tumorsmentioning
confidence: 90%
See 1 more Smart Citation
“…Tumor endothelial-specific expression of Robo4 in adults reveals that this plasma membrane protein represents an antitumor target for immunotherapeutic approaches, such as vaccination. Robo4-Fc-vaccinated mice showed retarded lung carcinoma growth, increased vascular leakage and intensified inflammation compared with control Fc-immunized mice [110]. Robo4 vaccination with alum adjuvant, a mild inducer of Th2-dependent antibody responses, also reduced tumor growth via an antibody-mediated mechanism, particularly an IgG1-mediated mechanism, instead of cytotoxic T-cell responses.…”
Section: Robo4 and Tumorsmentioning
confidence: 90%
“…Robo4 expression was initially detected in the vasculature at sites of active angiogenesis, including the placenta and various tumors [5]. Many subsequent studies have investigated Robo4 expression in physiological and pathological angiogenesis and revealed that Robo4 is involved in regulating angiogenesis during vascular development [31,49,108] in tumors [11,[109][110][111] and during ocular neovascularization [10,25,50,112,113].…”
Section: The Function Of Robo4 In Angiogenesismentioning
confidence: 99%
“…Besides endothelial cells, Robo4 is also expressed in hematopoietic stem cells and regulates their trafficking10111213. The highly endothelial-specific Robo4 expression has prompted considerable interest in this molecule to selectively target or image tumour vascularization9141516.…”
mentioning
confidence: 99%
“…Injection of this conjugate together with an appropriate adjuvant resulted in the induction of a strong antibody response against the self-antigen. This strategy seems now very successful as a similar approach was recently published by Zhuang et al on vaccination against the angiogenesis marker robo4 [ 7 ]. Major advantages of such vaccination approaches are (i) that a polyclonal antibody response is induced, which has better antigen neutralizing capacities; (ii) that vaccines do not require to be frequently administered, as is the case with monoclonal antibodies and small molecule drugs, and (iii) that vaccination provides an extremely cost effective strategy, which can be up to a hundred times less expensive than a monoclonal antibody therapy, due to the low amount of protein required for immunization.…”
mentioning
confidence: 88%